Trignometric Horrors I

Geometry Level 3

α \alpha = tan 2 π 7 tan 4 π 7 + tan 4 π 7 tan 8 π 7 + tan 8 π 7 tan 2 π 7 \tan { \frac { 2\pi }{ 7 } } \cdot \tan { \frac { 4\pi }{ 7 } } +\tan { \frac { 4\pi }{ 7 } } \cdot \tan { \frac { 8\pi }{ 7 } } +\tan { \frac { 8\pi }{ 7 } } \cdot \tan { \frac { 2\pi }{ 7 } }

Find the absolute value α \left| \alpha \right| .


The answer is 7.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

If we take θ = 2 π 7 \theta=\dfrac{2\pi}{7} , then we need to evaluate α = tan θ + tan 2 θ + tan 4 θ \alpha=\tan\theta+\tan2\theta+\tan4\theta we observe that θ + 2 θ + 4 θ = 2 π \theta+2\theta+4\theta=2\pi . So, we have cos ( θ + 2 θ + 4 θ ) = 1 cos θ cos 2 θ cos 4 θ ( 1 α ) = 1 \cos(\theta+2\theta+4\theta)=1\Rightarrow \cos\theta\cos2\theta\cos4\theta(1-\alpha)=1 Now, cos θ cos 2 θ cos 4 θ = sin 8 θ 8 sin θ = 1 / 8 \cos\theta\cos2\theta\cos4\theta=\dfrac{\sin 8\theta}{8\sin\theta}=1/8 . Hence we get α = 1 8 = 7 α = 7 \alpha=1-8=-7\Rightarrow |\alpha|=\boxed{7}

Pi Han Goh
Nov 28, 2014

Consider the equation cos ( 7 z ) = 1 \cos(7z) = -1 , by the Chebyshev Polynomial of the First Kind , letting y = cos ( z ) y = \cos(z) . We have

64 y 7 112 y 5 + 56 y 3 7 y + 1 = 0 64y^7 - 112y^5 + 56y^3 - 7y + 1 = 0

Because y = 1 y=-1 is a solution, we can factor out the expression, and knowing that cos ( π 7 ) , cos ( 2 π 7 ) , cos ( 3 π 7 ) , , cos ( 6 π 7 ) \cos \left ( \frac {\pi}{7} \right ), \cos \left ( \frac {2\pi}{7} \right ), \cos \left ( \frac {3\pi}{7} \right ) , \ldots , \cos \left ( \frac {6 \pi}{7} \right ) are roots of the sextic equation. Finally the equation factors to

( y + 1 ) ( 8 y 3 4 y 2 4 y + 1 ) 2 = 0 (y+1)(8y^3 - 4y^2 - 4y + 1)^2 = 0

The cubic equation has a multiplicity of 2 2 because cos ( π 7 ) = cos ( 6 π 7 ) , cos ( 2 π 7 ) = cos ( 5 π 7 ) , cos ( 3 π 7 ) = cos ( 4 π 7 ) \cos \left ( \frac {\pi}{7} \right ) = -\cos \left ( \frac {6\pi}{7} \right ), \cos \left ( \frac {2\pi}{7} \right ) = -\cos \left ( \frac {5\pi}{7} \right ), \cos \left ( \frac {3\pi}{7} \right ) = -\cos \left ( \frac {4\pi}{7} \right )

The cubic equation below has roots cos ( π 7 ) , cos ( 2 π 7 ) , cos ( 3 π 7 ) \cos \left ( \frac {\pi}{7} \right ), \cos \left ( \frac {2\pi}{7} \right ), \cos \left ( \frac {3\pi}{7} \right )

8 y 3 4 y 2 4 y + 1 = 0 8y^3 - 4y^2 - 4y + 1 = 0

With a further substitution of x = 1 y x = \frac {1}{y} and some simplification. We have another cubic equation with roots sec ( π 7 ) , sec ( 2 π 7 ) , sec ( 3 π 7 ) \sec \left ( \frac {\pi}{7} \right ), \sec \left ( \frac {2\pi}{7} \right ), \sec \left ( \frac {3\pi}{7} \right )

x 3 4 x 2 4 x + 8 = 0 x^3 - 4x^2 - 4x + 8 = 0

Denote f ( x ) = x 3 4 x 2 4 x + 8 f(x) = x^3 - 4x^2 - 4x + 8 , then f ( x ) = 0 f(\sqrt{x}) = 0 has roots sec 2 ( π 7 ) , sec 2 ( 2 π 7 ) , sec 2 ( 3 π 7 ) \sec^2 \left ( \frac {\pi}{7} \right ), \sec^2 \left ( \frac {2\pi}{7} \right ), \sec^2 \left ( \frac {3\pi}{7} \right )

x x 4 x 4 x + 8 = 0 x \sqrt{x} - 4x - 4\sqrt{x} + 8 = 0

x ( x 4 ) 2 = ( 4 x 8 ) 2 \Rightarrow x(x-4)^2 = (4x-8)^2

x 3 24 x 2 + 80 x 64 = 0 \Rightarrow x^3 - 24x^2 + 80x - 64 = 0

By Vieta's Formula, we have

sec 2 ( π 7 ) + sec 2 ( 2 π 7 ) + sec 2 ( 3 π 7 ) = ( 24 ) = 24 \sec^2 \left ( \frac {\pi}{7} \right ) + \sec^2 \left ( \frac {2\pi}{7} \right ) + \sec^2 \left ( \frac {3\pi}{7} \right ) = -(-24) = 24

Using the trigonometric identity: tan 2 ( A ) + 1 = sec 2 ( A ) \tan^2 (A) + 1 = \sec^2 (A) , we obtain

tan 2 ( π 7 ) + tan 2 ( 2 π 7 ) + tan 2 ( 3 π 7 ) = 21 \tan^2 \left ( \frac {\pi}{7} \right ) + \tan^2 \left ( \frac {2\pi}{7} \right ) + \tan^2 \left ( \frac {3\pi}{7} \right ) = 21

Similarly, by Vieta's Formula

sec 4 ( π 7 ) + sec 4 ( 2 π 7 ) + sec 4 ( 3 π 7 ) = 2 4 2 2 80 = 416 \sec^4 \left ( \frac {\pi}{7} \right ) + \sec^4 \left ( \frac {2\pi}{7} \right ) + \sec^4 \left ( \frac {3\pi}{7} \right ) = 24^2 - 2 \cdot 80 = 416

( tan 2 ( π 7 ) + 1 ) 2 + ( tan 2 ( 2 π 7 ) + 1 ) 2 + ( tan 2 ( 3 π 7 ) + 1 ) 2 = 416 \Rightarrow \left ( \tan^2 \left ( \frac {\pi}{7} \right ) + 1 \right )^2 + \left ( \tan^2 \left ( \frac {2\pi}{7} \right )+ 1 \right )^2 + \left ( \tan^2 \left ( \frac {3\pi}{7} \right ) + 1 \right )^2 = 416

tan 4 ( π 7 ) + tan 4 ( 2 π 7 ) + tan 4 ( 3 π 7 ) = 371 \Rightarrow \tan^4 \left ( \frac {\pi}{7} \right ) + \tan^4 \left ( \frac {2\pi}{7} \right ) + \tan^4 \left ( \frac {3\pi}{7} \right ) = 371

Now, we apply the trigonometric identities: tan ( A ) = tan ( π A ) \tan(A) = -\tan( \pi - A) and tan ( A ) = tan ( π + A ) \tan(A) = -\tan(\pi + A) , then we have the two equations

tan 2 ( 8 π 7 ) + tan 2 ( 2 π 7 ) + tan 2 ( 4 π 7 ) = 21 \tan^2 \left ( \frac {8\pi}{7} \right ) + \tan^2 \left ( \frac {2\pi}{7} \right ) + \tan^2 \left ( \frac {4\pi}{7} \right ) = 21

tan 4 ( 8 π 7 ) + tan 4 ( 2 π 7 ) + tan 4 ( 4 π 7 ) = 371 \tan^4 \left ( \frac {8\pi}{7} \right ) + \tan^4 \left ( \frac {2\pi}{7} \right ) + \tan^4 \left ( \frac {4\pi}{7} \right ) = 371

Note that the sum of the three numbers 8 π 7 , 2 π 7 , 4 π 7 \frac {8\pi}{7}, \frac {2\pi}{7}, \frac {4\pi}{7} is equals to 2 π 2\pi . By expanding the compound angle formula tan ( A + B + C ) = 0 \tan(A+B+C) = 0 , we get

tan ( A ) + tan ( B ) + tan ( C ) = tan ( A ) tan ( B ) tan ( C ) \tan(A) + \tan(B) + \tan(C) = \tan(A) \tan(B) \tan(C)

Now consider a cubic equation g ( x ) g(x) with roots tan ( 8 π 7 ) , tan ( 2 π 7 ) , tan ( 4 π 7 ) \tan \left ( \frac {8\pi}{7} \right ) , \tan \left ( \frac {2\pi}{7} \right ) , \tan \left ( \frac {4\pi}{7} \right )

Using Newton's Sum method, denote S n S_n and P n P_n as the n th n^{\text{th} } symmetric sum of roots of g ( x ) g(x) and sum of n th n^\text{th} powers of roots of g ( x ) g(x) respectively

Then S 1 = P 1 , 21 = P 2 = S 1 2 2 S 2 S_1 = P_1 , 21 = P_2 = S_1 ^2 - 2S_2 and S 1 = S 3 S_1 = S_3 from above

Consider the expansion

a 4 + b 4 + c 4 = ( a 2 + b 2 + c 2 ) 2 2 ( a b + a c + b c ) 2 + 4 a b c ( a + b + c ) a^4 + b^4 + c^4 = (a^2 + b^2 + c^2)^2 - 2(ab+ac+bc)^2 + 4abc(a+b+c)

P 4 = P 2 2 2 S 2 2 + 4 S 1 2 \Rightarrow P_4 = P_2 ^2 - 2 S_2 ^2 + 4 S_1 ^2

371 = 2 1 2 2 S 2 2 + 4 S 1 2 \Rightarrow 371 = 21^2 - 2 S_2 ^2 + 4 S_1 ^2

35 = S 2 2 2 S 1 2 \Rightarrow 35 = S_2 ^2 - 2 S_1 ^2

Solving the two equations 21 = S 1 2 2 S 2 , 35 = S 2 2 2 S 1 2 21 = S_1 ^2 - 2S_2, 35 = S_2 ^2 - 2 S_1 ^2 simultaneously, denoting P , Q P,Q as S 1 , S 2 S_1, S_2 respectively

We have 21 = P 2 2 Q , 35 = Q 2 2 P 2 21 = P^2 - 2Q, 35 = Q^2 - 2P^2 , add twice the first equation to the second, we obtain 77 = Q 2 4 Q 81 = ( Q 2 ) 2 Q = 11 , 7 77 = Q^2 - 4Q \Rightarrow 81 = (Q-2)^2 \Rightarrow Q = 11,-7

Hence α = Q = S 2 \alpha = Q = S_2 is the sum of negative numbers because the tangent of both 4 π 7 \frac {4\pi}{7} and 8 π 7 \frac {8\pi}{7} yields a negative value.

This means that α = 7 \alpha = -7 only. So the answer is 7 \boxed{7}

This problem should be at least a level 4...

Alex Wang - 6 years, 6 months ago

Log in to reply

i think there should be some simpler way to do this using trigonometry.

Priyesh Pandey - 6 years, 6 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...